2021
DOI: 10.1007/s40684-021-00363-2
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of a Plastic Part Injected with Recycled Polypropylene: A Comparison with Alternative Virgin Materials

Abstract: The consumption of plastic materials, especially polypropylene, has increased exponentially in recent decades, and it is now stabilized in its historic maximum [1]. This growth is due to the increase in technological possibilities for this type of material, the rise of consumption in society, and the new manufacturing techniques as additive manufacturing [2][3][4]. This culture of consumism makes it necessary to establish sustainable environmental management that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 78 publications
0
4
0
1
Order By: Relevance
“…For a better understanding of this methodology, it will be applied to a specific case, which involves the design of a plastic support-a component with which the authors already have experience. Previous research [56][57][58][59] has demonstrated the feasibility of replacing fiber-reinforced polyamide with talc-filled polypropylene and subsequently with recycled polypropylene. The current part thickness is 1.8 mm.…”
Section: Methodsmentioning
confidence: 99%
“…For a better understanding of this methodology, it will be applied to a specific case, which involves the design of a plastic support-a component with which the authors already have experience. Previous research [56][57][58][59] has demonstrated the feasibility of replacing fiber-reinforced polyamide with talc-filled polypropylene and subsequently with recycled polypropylene. The current part thickness is 1.8 mm.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Galve, Elduque, Pina, and Javierre (2021) showed that for example recycled PP has a significantly lower environmental impact compared to virgin PP. The overall environmental impact (ReCiPe endpoint) was 29.8% lower and the carbon footprint was reduced by 42.8% (Galve et al, 2021). Therefore, changing the material from virgin PP to recycled PP is a good strategy to reduce the impact of the syringe.…”
Section: Circular Materials Vs Virgin Materialsmentioning
confidence: 99%
“…There are many records of LCA applications to quantify impacts derived from the use of recycled plastics. In one of the most recent, Galve et al [33] observed that replacing virgin PP with a recycled form could improve the global environmental performance of polymeric components by up to 30%. Following a parallel trend, Agarski et al [34] concluded that mold manufacturing and electricity consumption were the main focuses of the lifecycle impact of HDPE caps in a study of parts manufacture in Serbia.…”
Section: Introductionmentioning
confidence: 99%